MRI Abnormalities Are Common In Little League Player's Elbows: A Longitudinal Study. Issue 7 (18th July 2016) - Pennock, Andrew T.; Roocroft, Joanna Helena; Bastrom, Tracey P.; Kruk, Peter
Objectives: Youth baseball is extremely popular, but it has been associated with elbow pain and pathology. The purpose of this study was to examine pre- and post-season Magnetic Resonance Imaging (MRI) changes in Little League baseball players and correlate these findings with the players' throwing history and physical exams. Methods: A prospective study of Little League players age 10 -13 years was performed. Players were recruited prior to the start of the season and underwent bilateral elbow MRI. All players underwent a physical exam and responded to a questionnaire addressing their playing history and arm pain. At the end of the season, the players underwent repeat physical exam and MRI of their throwing arm. MRIs were read by two blinded radiologists. During the season, player statistics including innings played and pitch counts were recorded. Physical exam findings and players statistics were compared between subjects with and without MRI changes utilizing chi-square and ANOVA techniques. Results: Twenty-six players were enrolled. On pre-season MRI, nine players (35%) had 12 positive MRI findings; edema of the medial epicondyle (ME) apophysis (7), fragmentation of ME (2), and edema of the sublime tubercle (3). The two factors associated with a positive MRI were year round play (47% vs 11%, p<0.01) and working with a private coach (71% vs 21%, p=0.02). A history of pain was also associated with year round play and a private coach (p<0.05). Loss of internal rotation was associated with an abnormal MRI (p = 0.04). Post-season, 25 players returned for follow-up. Ten players (40%) had an abnormal MRI of which 8 (32%) had new/worsening findings. There was a significant difference in distal humeral physeal width measured pre- to post-season (1.54 mm vs 2.31 mm p<0.001). There was a significant decrease in internal rotation measured pre- to post-season of the shoulder in all patients regardless of MRI findings (62° vs 43°, p=0.001). Pitch counts, player position, and throwing curve balls/sliders were not significantly associated with pain or MRI abnormality post season (p >0.10). Descriptively, 60% of self-reported pitchers/catchers had post season MRI findings versus 40% of other field positions (p=0.3). Conclusion: Pre-season and post-season MRI abnormalities of the medial elbow are common in Little League baseball players. While Little League pitching guidelines are intended to decrease overuse injuries, our data indicate that further refinement of these guidelines addressing year round play, pain and private coaching should be considered.